Estado cognitivo y nivel educativo en el adulto mayor del centro diurno del adulto mayor de Vilcabamba CAMVIL, periodo 2022. - Rivera Murillo, Francisco Enrique (2022)
Cognitive status refers to the condition of neuropsychological functioning in relation to development in the environment. From 65 years of age, at the brain level a cognitive deterioration typical of biochronological age occurs, which depending on the psychological development may be classified as normal or pathological. The objective of this study was: To analyze the relationship between the cognitive status and the educational level of the elderly in the Vilcabamba day center for the elderly, it was framed in a mixed, descriptive, and cross-sectional approach, with a population of 16 older adults, based on the use of different methods. To collect the proper information, the psychological instrument Mini-mental cognitive test and a semi-structured interview were applied; and to relate the variables, the Spearman's Chi-square test was used. After analyzing the data, it was possible to determine that the cognitive status of older adults corresponds to 56.3% normal, 18.8% mild, and 25% moderate; Regarding the educational level, 87.5% have the level of basic general education at most, and 12.5% have no schooling level. Regarding the correlation of variables, a negative relationship was found between cognitive status and educational level. Regarding the application of the interview, the population that is composed by older adults between 65 and 94 years of age; mostly widowers; with a lifestyle associated with scarce economic resources which has limited them educationally and socially throughout their lives; among the work occupations and daily performances are agriculture and housewives; a quarter of them suffer from diseases such as hypertension, osteoporosis, prostate and thyroid; Likewise, they present auditory, visual, and physical limitations that do not deprive them of their autonomy. In conclusion, knowing that older adults have a mostly healthy cognitive state, being between normal, mild and moderate, which is according to their age and does not affect their daily lives, in addition to reaching a low educational level as a result of the socioeconomic limitations present At that time, the null hypothesis is accepted H0 = Cognitive status is not related to the educational level of the older adult. Keywords: older adult, aging, cognitive status, education, cognitive reserve.